How do memory modules differentially contribute to familiarity and recollection?. (3rd January 2020) - Hakobyan, Olya; Cheng, Sen
Abstract: We fully support dissociating the subjective experience from the memory contents in recognition memory, as Bastin et al. posit in the target article. However, having two generic memory modules with qualitatively different functions is not mandatory and is in fact inconsistent with experimental evidence. We propose that quantitative differences in the properties of the memory modules can account for the apparent dissociation of recollection and familiarity along anatomical lines.